2013
DOI: 10.1016/j.bone.2012.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Failure to generate bone marrow adipocytes does not protect mice from ovariectomy-induced osteopenia

Abstract: A reciprocal association between bone marrow fat and bone mass has been reported in ovariectomized rodents, suggesting that bone marrow adipogenesis has a negative effect on bone growth and turnover balance. Mice with loss of function mutations in kit receptor (kitW/W-v) have no bone marrow adipocytes in tibia or lumbar vertebra. We therefore tested the hypothesis that marrow fat contributes to development of osteopenia by comparing the skeletal response to ovariectomy (ovx) in growing wild type (WT) and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 62 publications
1
56
1
Order By: Relevance
“…Adipocytes and osteoblasts are derived from the same bone marrow mesenchymal precursor and a reciprocal association between osteoblast number and adipocyte number has often been noted, giving rise to the hypothesis that bone marrow adipocytes may either antagonize osteoblast production or, alternatively, generation of adipocytes precludes generation of osteoblasts (Akune, et al 2004). Other studies suggest that adipocyte and osteoblast number in bone marrow can be independently regulated (Iwaniec and Turner 2013; Menagh et al 2010). Bartell et al (2011) reported that intracerebroventricular administration of leptin to ob/ob mice increases expression of SP7, a transcription factor critical for osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes and osteoblasts are derived from the same bone marrow mesenchymal precursor and a reciprocal association between osteoblast number and adipocyte number has often been noted, giving rise to the hypothesis that bone marrow adipocytes may either antagonize osteoblast production or, alternatively, generation of adipocytes precludes generation of osteoblasts (Akune, et al 2004). Other studies suggest that adipocyte and osteoblast number in bone marrow can be independently regulated (Iwaniec and Turner 2013; Menagh et al 2010). Bartell et al (2011) reported that intracerebroventricular administration of leptin to ob/ob mice increases expression of SP7, a transcription factor critical for osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cBMAT in distal tibia is similar between sexes 18, 21, 27 . As in humans, estrogen deficiency in rodents is a strong stimulus for BMAT development 18, 28 , and whereas ovariectomy increases cBMAT of distal tibia by ~30%, the expansion of proximal tibial rBMAT is far more extensive 18, 28 . Estrogen is not only necessary to restrain accumulation of BMAT, but exogenous administration of estrogen is sufficient to stimulate rapid loss of marrow adiposity in tibia 29 .…”
Section: Development and Regulation Of Bmat In Humans And Rodentsmentioning
confidence: 98%
“…Specifically, removal of the pituitary gland in rats causes robust increases in MAT that are rescued by administration of exogenous growth hormone, but not intermittent PTH, 17β-estradiol, or IGF-1 [65]. Estrogen deficiency [66,67], FGF-21 [68] and glucocorticoids [69,70] also promote MAT formation. Of these, increases in circulating glucocorticoids may be necessary for MAT accumulation with CR [4].…”
Section: Endocrine Regulation Of Mat Expansion In Metabolic Diseasementioning
confidence: 99%